Pengenalan Teknologi Informasi Untuk Generasi Milenial di SMK Swasta Nurcahaya Medan - Sinar Sinurat; Eferoni Ndururu; Riswan Limbong (JPM: Jurnal Pengabdian Masyarakat, 2023)
The introduction of technology to the millennial generation is very behind in making good use of technology. Most millennials use technology incorrectly. In terms of information technology is very helpful in supporting learning and being able to interact with others. And most people misuse information technology properly and many are still not familiar with the components used in building information technology such as hardware, software and types of technology. It causes misuse of devices or types of technology